2022
DOI: 10.1007/s00170-022-09543-z
|View full text |Cite
|
Sign up to set email alerts
|

3D finite element simulation for tool temperature distribution and chip formation during drilling of Ti6Al4V alloy

Abstract: A comprehensive 3D finite element simulation study has been conducted to investigate the tool temperature distribution along cutting edge and chip formation during drilling of Ti6Al4V alloy by using commercial finite element software Abaqus/Explicit. The Johnson-Cook material constitutive model and material failure criterion were implemented across the formulations to achieve the tool temperature and chip formation in the drilling process. The effect of different mesh sizes on simulation results was also analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…As a result, this study was performed to simulate the in uence of tool nose radius, clearance angle, and rake angle in the machining of Ti alloy. Few investigations have been conducted to determine the relationships between cutting parameters and cutting forces when cutting titanium alloys using FEM [19,37,49,50,51]. The results presented further demonstrate that the JC damage criteria are commonly used in simulating the machining of titanium alloys and in modeling the formation of segmented chips [19,52,53].…”
Section: Fea Simulationmentioning
confidence: 86%
“…As a result, this study was performed to simulate the in uence of tool nose radius, clearance angle, and rake angle in the machining of Ti alloy. Few investigations have been conducted to determine the relationships between cutting parameters and cutting forces when cutting titanium alloys using FEM [19,37,49,50,51]. The results presented further demonstrate that the JC damage criteria are commonly used in simulating the machining of titanium alloys and in modeling the formation of segmented chips [19,52,53].…”
Section: Fea Simulationmentioning
confidence: 86%
“…Among the known constitutive equations (material models) used in numerical cutting models [53], the Johnson-Cook equation [54] has become the most popular. This is due to the relative simplicity and clarity of this constitutive equation, which was the reason for its application in 3D cutting models, particularly for modeling the drilling process [55,56]. Various methods were used to determine the parameters of the constitutive equation applied in numerical models of drilling: borrowing from known publications (see, for example, [57,58]), determination of these parameters from the results of the orthogonal cutting process and experimental studies (see, for example, [59][60][61]), and others.…”
Section: Methods For the Determination Of Thermal Characteristics In ...mentioning
confidence: 99%
“…The most common one is the Johnson-Cook constitutive equation, which has been very often used in numerical models of the cutting process [52]. The application of the machined material model in the form of this equation has been mainly used in three-dimensional finite element models of material machining with end tools, in particular, models of drilling [53,54], milling [55,56], and other cutting processes. Moreover, the parameters of the constitutive equation were mostly taken from previously conducted studies, for example, those found in [57,58].…”
Section: Methods For the Determination Of Kinetic Characteristics In ...mentioning
confidence: 99%
“…Experimental data (see, for example, [64]) were used as target values of the cutting process characteristics. To determine the parameters of contact interaction between the tool and the machined material [65], previously conducted studies on the estimation of friction parameters [54,56], as well as heat flows in the cutting zones [66] have been used in the vast majority of cases. For the numerical modeling of cutting processes with hard-to-machine materials, such as, for example, titanium and nickel alloys, it is necessary to know the fracture parameters of the machined material [67].…”
Section: Methods For the Determination Of Kinetic Characteristics In ...mentioning
confidence: 99%